SECTORAL DECOMPOSITION ANALYSIS: THE CONTRIBUTION OF THE TOURISM SECTOR TO EAST JAVA'S GRDP THROUGH TOURIST, HOTEL, AND RESTAURANT COMPONENTS : ANALISIS DEKOMPOSISI SEKTORAL: KONTRIBUSI SEKTOR PARIWISATA MELALUI KOMPONEN WISATAWAN, PERHOTELAN, DAN RESTORAN TERHADAP PDRB JAWA TIMUR - Istiandari, Debby Nindya; Juventi, Meilani Dwi; Adhitya, Bagus; Fatmawati, Anisa; Zumaeroh, Zumaeroh (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2026)
This study examines the influence of the tourism sector on the Gross Regional Domestic Product (GRDP) of East Java Province. Given that tourism is a crucial sector in driving regional economic growth through its contributions to local revenue, employment, and investment, this research aims to analyze the impacts of tourist arrivals, hotel counts, and restaurant numbers on GRDP to support effective tourism development policies. Adopting a quantitative approach, the study utilizes secondary panel data consisting of 190 observations across several regencies and cities in East Java for the 2018–2022 period, sourced from the Department of Culture and Tourism and the Central Statistics Agency of East Java Province. Data analysis was conducted using EViews 10 software with the Fixed Effects Model (FEM) method to examine the relationships between the independent variables and the dependent variable (GRDP). The results demonstrate that simultaneously, tourist arrivals, hotel counts, and restaurant numbers significantly influence GRDP. Partially, each independent variable also has a significant effect on GRDP. These findings confirm the important role of tourism sector development in regional economic growth.